From the Greek Medical Manuscripts of the Ottoman Empire to the Pharmacopoeia I of the Greek State: Pharmacy and Political Change in Southeastern Europe - Barlagiannis , Athanasios; Seriatou, Penelope; Seirinidou, Vaso (The Historical Review/La Revue Historique, 2023)
The article studies the transition from the medical manuscripts that circulated as a means of knowledge preservation and professional regulation in the early modern Greek world to the first edited pharmacopoeia of the Greek state in 1837. The transition is examined in parallel to the changes in the political, scientific and professional domains attested in southeastern Europe from the eighteenth to the middle of the nineteenth centuries. After an overview of the Greek state’s legal interventions in the pharmaceutical trade, in the context of which the pharmacopoeia was promulgated, and of the efforts to translate the pharmaceutical terms by court physicians and pharmacists, the article compares the materia medica of the Ελληνική Φαρμακοποιΐα (Greek Pharmacopoeia) with that of two medical manuscripts that circulated in the period before the formation of the Greek state. By studying the process of incorporation and/or exclusion of pharmaceutical ingredients during the establishment of a new legal culture and of a more formal way of regulating pharmacy in the southeastern Balkans, the article discusses important issues in the history of pharmacy, especially its relationship to politics, ideology and professional rivalries.